Differential effect of FHM2 mutation on synaptic plasticity in distinct hippocampal regions. (September 2019) - Iure, Antonio de; Mazzocchetti, Petra; Bastioli, Guendalina; Picconi, Barbara; Costa, Cinzia; Marchionni, Ivan; Casari, Giorgio; Tozzi, Alessandro; Pietrobon, Daniela; Calabresi, Paolo
Introduction: Familial hemiplegic migraine 2 is a pathology linked to mutation of the ATP1A2 gene producing loss of function of the α2 Na + /K + -ATPase (NKA). W887R/+ knock-in (KI) mice are used to model the familial hemiplegic migraine 2 condition and are characterized by 50% reduced NKA expression in the brain and reduced rate of K + and glutamate clearance by astrocytes. These alterations might, in turn, produce synaptic changes in synaptic transmission and plasticity. Memory and learning deficits observed in familial hemiplegic migraine patients could be ascribed to a possible alteration of hippocampal neuronal plasticity and measuring possible changes of long-term potentiation in familial hemiplegic migraine 2 KI mice might provide insights to strengthen this link. Results: Here we have investigated synaptic plasticity in distinct hippocampal regions in familial hemiplegic migraine 2 KI mice. We show that the dentate gyrus long-term potentiation of familial hemiplegic migraine 2 mice is abnormally increased in comparison with control animals. Conversely, in the CA1 area, KI and WT mice express long-term potentiation of similar amplitude. Conclusions: The familial hemiplegic migraine 2 KI mice show region-dependent hippocampal plasticity abnormality, which might underlie some of the memory deficits observed in familial migraine.